Farmers' Motivation on Seaweed Cultivation in Kawite-Wite Village Kabawo Sub-District Muna District - Salahuddin, Salahuddin; Buana, Tjandra; Parto, Parto (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2020)
This study aimed to determine farmers’ motivation level and farmers' activities in seaweed cultivation in Kawite-Wite Village, Kabawo Sub-District, Muna District. The sample in this study was determined by simple random sampling. This study used interval scale analysis. The results showed that the farmers’ motivation level and farmers' activities in seaweed cultivation in Kawite-Wite Village, Kabawo Sub-District of Muna District have been carried out well.